Chinese Muslim Predicament in Indonesia's Post Reformation - Eko Putro, Zainal Abidin (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2014)
Indonesian Chinese with no exception Chinese Muslim in Indonesia has stepped into a considerable freedom during the current Reformation era. As like as many other Chinese Indonesians who take a part in creating integration model without abandoning their ethnic identity, Chinese Muslim have also shown similar endeavor. However, within the context of post-Reformation democracy, it seems that Chinese Muslim solely fights against any other Indonesian Chinese group and other Muslim community in Indonesia at the same time. Study about Chinese Muslim in Indonesia after Reformation is briefly undertaken ranging from its political contexts, cultural, and economy alike. Some scholars who interest in its cultural realm have been dealt with the important role of Chinese in spreading Islam into Nusantara in 14th Century. Here, Admiral Cheng Ho was an influential figure to introduce Islam to local people in northern coastal area of Java Island. It sounds that it is unlike with many other scholars who convince that Islam came to Java in the hand of Gujarat traders. This paper tries to explore the existence of Chinese Muslim in Jakarta during the current Post Reformation era. To complete this paper, I try to combine data that taken from in-depth interview with literature review and personal observation on some people and signs of Chinese Muslim in Jakarta.